Constructing and applying a tiered family engagement strategy for managing neurogenic bowel dysfunction in TSCI patients - Li, Hongyan; Wang, Zhaoxuan; Ding, Jia; Wang, Qian; Wang, Ruiling (Frontiers in Neurology, 2026)
BackgroundNeurogenic bowel dysfunction (NBD) severely impairs life quality after thoracic spinal cord injury (TSCI). In this 133-patient trial, we evaluated whether a literacy-adaptive, family-centred programme improves outcomes beyond guideline care.MethodsIn this single-centre, prospective, stratified, randomised controlled trial, 137 T6–T12 TSCI patients and their primary caregivers were assigned to routine follow-up (n = 69) or a tiered family-engagement intervention matched to caregiver educational level (n = 68). Primary endpoint was change in NBD score; secondary endpoints were caregiver execution score, Zarit Burden Interview (ZBI) and SF-36. Assessments occurred at discharge, 6 and 12 months (intention-to-treat).ResultsAt 12 months, the intervention group showed a larger mean NBD reduction than controls (3.5 ± 4.8 vs. 2.6 ± 5.2) and greater improvements in execution (d = 1.55), ZBI (d = −1.33) and SF-36 (d = 0.88). Benefits increased step-wise from tertiary- to primary-education strata, with no significant effect among highly educated caregivers. No programme-related adverse events occurred.ConclusionTailoring NBD management to caregiver literacy yields clinically meaningful, durable gains in bowel function, caregiving competence, burden and patient quality of life, especially when baseline self-efficacy is low. Literacy-stratified discharge pathways should be integrated into rehabilitation practice.